The Effectiveness of Thermal Insulation of the Exterior Composite Walls of Buildings in Iraq Based on Different Materials and Climate Regions using Engineering Applications - Ali Raad Mohammed, Sepanta Naimi (International Journal of Intelligent Systems and Applications in Engineering, 2023)
U-value, or thermal efficiency, is a measure of the thermal characteristics of a building envelope and an essential criterion for assessing heat loss via building elements due to heat transfer. It is calculable based on the thermal qualities of the construction materials. By enhancing their thermal qualities, composite walls could help buildings meet stringent energy and environmental performance standards, such as those for practically zero-energy buildings (nZEB). Composite walls are preferable to traditional building methods due to their superiority in several areas, including durability, efficiency, cost, and the well-being of construction workers. Despite the benefits of this construction method, thermal bridges may arise in wall elements due to the high thermal conductivity of structural materials. Adding thermal insulation layers to composite walls is the focus of this research. To this end, four climatic regions in Iraq are used to conduct tests on various composite wall types. To calculate thermal transmittance, all that is needed are the indoor and outdoor air temperatures and the characteristics of the wall material. Exhaustive statistical research shows how Iraq’s climate directly impacts the building’s heat load and the effectiveness variations between insulating materials.